INFLUÊNCIA DE FRAGMENTOS DE CERRADO NA INFECÇÃO FÚNGICA EM ÁCAROS DE SERINGUEIRA - Demite, P.r. [UNESP]; Feres, R.j.f. [UNESP] (Instituto Biológico, 2022)
Fungi are the most common pathogens found in mites, being promising candidates for the biological control of these pests. Twenty-five samples were collected from rubber tree plantations adjacent to two fragments of cerrado vegetation, cerradão andriparianforest, in Itiquira, MT, Brazil. Five transects made 50 m apart were established for each plantation; the first transect was located on the edge, near the native cerrado area; the last transect was 200 m from the edge. Five plants from each transect, 25 m apart from each other were chosen. Fifty specimens of each of 3 phytophagous species (Calacarus heveae Feres, Phyllocoptruta seringueirae Feres, and Tenuipalpus heveae Baker) were collected and mounted on microcopy slides for the observation of epizooty. The same procedure was adopted in qualitative collections for the mites on the plants located in the fragments neighboring the rubber tree crop. A relationship was found to exist between the infection by fungi and the distance from the riparian forest. Moreover, in the 2 areas of neighboring native vegetation, mites were collected infected by Hirsutella thompsonii. These areas can serve as reservoirs of fungi, mainly in the period of the natural senescence of the leaves of the rubber 3 plantations.

Os fungos são os patógenos mais comuns encontrados em ácaros, sendo candidatos promissores para o controle biológico. Ao longo de um ano, foram realizadas 25 coletas em duas áreas de cultivo de seringueira, vizinhas de fragmentos de Cerrado, Cerradão e Mata Ripária, no Município de Itiquira, MT. Cinco transectos foram estabelecidos em cada seringal, distantes 50 m entre si, sendo um na borda com as áreas nativas e o último 200 m no interior de cada seringal. Em cada transecto, foram marcadas cinco plantas, distantes cerca de 25 m entre si. Em cada transecto, 50 indivíduos de três espécies de ácaros fitófagos (Calacarus heveae Feres, Phyllocoptruta seringueirae Feres e Tenuipalpus heveae Baker) foram coletados e montados em lâminas de microscopia, para a observação da epizootia nos ácaros. O mesmo procedimento foi adotado em coletas qualitativas para os ácaros presentes nas plantas localizadas nos fragmentos vizinhos aos seringais. Verificouse relação entre a infecção dos ácaros por fungos em relação à distância do fragmento de Mata Ripária. Além disso, nos 2 fragmentos vizinhos, foram coletados ácaros infectados por Hirsutella thompsonii. Essas áreas podem servir de reservatórios de fungos, principalmente no período da senescência natural das folhas das seringueiras.
INFLUENCE OF FRAGMENTS OF CERRADO VEGETATION IN FUNGAL INFECTION IN RUBBER-TREE MITES
Keywords: Acari; edge effect; Hevea brasiliensis; Hirsutella thompsonii; Neozygites; Acari; efeito de borda; Hevea brasiliensis; Hirsutella thompsonii; Neozygites